Bipolar Disorder and Multiple Sclerosis: A Case Series. (17th March 2014) - Sidhom, Youssef; Ben Djebara, Mouna; Hizem, Yosr; Abdelkefi, Istabrak; Kacem, Imen; Gargouri, Amina; Gouider, Riadh
Abstract : Background. The prevalence of psychiatric disturbance for patients with multiple sclerosis (MS) is higher than that observed in other chronic health conditions. We report three cases of MS and bipolar disorder and we discuss the possible etiological hypothesis and treatment options. Observations. All patients fulfilled the McDonald criteria for MS. Two patients were followed up in psychiatry for manic or depressive symptoms before developing MS. A third patient was diagnosed with MS and developed deferred psychotic symptoms. Some clinical and radiological features are highlighted in our patients: one manic episode induced by high dose corticosteroids and one case of a new orbitofrontal MRI lesion concomitant with the emergence of psychiatric symptoms. All patients needed antipsychotic treatment with almost good tolerance for high dose corticosteroids and interferon beta treatment. Conclusions. MRI lesions suggest the possible implication of local MS-related brain damage in development of pure "psychiatric fits" in MS. Genetic susceptibility is another hypothesis for this association. We have noticed that interferon beta treatments were well tolerated while high dose corticosteroids may induce manic fits.